Elements of bureaucracy: personal reflections on "going with the process" in Ethiopia. Issue 2 (17th February 2021) - Jackson, Ruth
ABSTRACT: Qualitative research is not just the study of words and meaning: researchers should also provide a critical reflection on theoretical or practical problems in the research process. This practical note is a reflexive account of some the author's personal experiences learning about bureaucratic process in Ethiopia. From opening a bank account as an "authentic" way to access money in 2007, to describing how to get a single document authenticated for a work permit ten years later, the author explores how bureaucratic encounters can become a meaningful and joyful way to interact with people met along the way.